Instrumen Hukum dalam Mendorong Pembangunan Internasional: Studi Kasus Penanggulangan Perdagangan Manusia di Thailand - Dody Molasy, Honest (Prodi Ilmu Hukum Fakultas Hukum Universitas Islam Jember, 2025)
This study examines how Thailand's law enforcement affects the achievement of Sustainable Development Goals (SDGs) related to reducing human trafficking. While the national legal framework aligns with international agreements like the Palermo Protocol, there are notable gaps between laws and their implementation. Research shows a strong link between effective law enforcement and progress in SDG-5 (gender equality) and SDG-8 (decent work and economic growth), with an 18% rise in formal employment for women in areas with better enforcement. However, a heavy reliance on criminal prosecution, which accounts for about 70% of anti-trafficking spending, proves ineffective without comprehensive victim support and prevention programs. Data reveals that 65% of rehabilitated victims re-offend due to limited economic opportunities and social support. Although regional cooperation through ASEAN and the UNODC has enhanced cross-border responses, only one-third of planned actions have been executed, hindered by regulatory inconsistencies and varying technical capacities. Additional challenges include the absence of a specific child-protection law for those under fifteen and a shortage of provincial case-handling units. The study recommends adopting a unified preventive approach, enhancing inter-agency collaboration, and implementing results-oriented monitoring to align law with practice, thereby supporting sustainable development in Thailand.